The impact of criminal punishment on the public employee in the crime of bribery in Iraqi law and Algerian law (Comparative study) - Hliyil, Jaafar Mohammed (Edelweiss Applied Science and Technology, 2024)
This research examines the impact of criminal punishment on public employees who commit bribery, comparing Iraqi and Algerian legal systems. The study highlights the responsibilities of public employees and how criminal penalties, whether original, subsidiary, or precautionary, affect their legal and professional status. Iraqi and Algerian laws emphasize the importance of maintaining job integrity and public trust. The study explores penalties like imprisonment, fines, and confiscation alongside precautionary measures that limit employees’ rights or restrict their duties. The comparative analysis reveals legislative gaps, particularly in addressing precautionary measures tailored for public employees. While Algerian law focuses on preventing criminal danger through general precautionary measures, Iraqi law adopts a more structured approach to employee misconduct and subsequent disciplinary actions. The research concludes with recommendations to enhance accountability, prevent bribery, and protect public office integrity. Proposals include increasing employee awareness, improving salaries to reduce corruption incentives, and strengthening legislative frameworks to address preventive and rehabilitative measures. This study underscores the necessity of balancing legal punishment with precautionary mechanisms to combat bribery effectively and safeguard public administration’s efficiency and reputation.